2014
DOI: 10.1080/09540253.2014.901719
|View full text |Cite
|
Sign up to set email alerts
|

Constructing men who teach: research into care and gender as productive of the male primary teacher

Abstract: This paper argues that in order to begin loosening the ties that bind care and gender in primary education, we need to re-examine the knowledge sought and found by educational research about teachers. The focus is primarily on how we understand men who teach. Through an examination of two scholarly texts -Ashley, M., and J. Lee [2003. Women Teaching Boys: Caring and Working in the Primary School. Stoke-on-Trent: Trentham] and King, J. [1998. Uncommon Caring: Learning from Men Who Teach Young Children. New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…
“A foundation of teachers’ professional identities, as well as their contemporary working conditions, is gender” (Pulsford, , p. 215).
…”
mentioning
confidence: 99%
“…
“A foundation of teachers’ professional identities, as well as their contemporary working conditions, is gender” (Pulsford, , p. 215).
…”
mentioning
confidence: 99%
“…Therefore, seclusion was a gendered school landscape, involving gendered expectations about care, nurture and emotional labour (O'Brien, ; Pulsford, ). This is perhaps unsurprising, given that gender is central to caring throughout the education sector (James, ; Milligan & Wiles, ; Rogers & Weller, ).…”
Section: Resultsmentioning
confidence: 99%
“…This might have helped them to overcome some of the barriers men encounter when they choose a gendertyped profession. Significant others' references to gender stereotypes are, as other studies have revealed, one of the most powerful factors that can deter particularly male adolescents from choosing a non-traditional career (Simpson 2004;Phipps 2007;Pulsford 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The reluctance of men entering the field of teaching has traditionally been linked to the debate around 'feminisation' and 'masculinity' of schooling. From a feminist and constructivist perspective, masculinity is a social construction in a constant state of flux where teachers are constantly negotiating 'becoming and being' a male teacher in a female-dominated profession (King 1998;Francis 2008;Haase 2008;Pulsford 2014). Historically, elementary school teaching has never been an attractive option for working-class men due to the construction of masculinity that is strongly related to the importance of physical labour in opposition to intellectual work (Skelton 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation